Measurement Techniques and Practices of Colloid and Interface Phenomena - Abe, Masahiko (Springer Nature Singapore : Imprint: Springer, 2019)
This book is a manual of measurement of colloids and interfaces designed especially for new researchers who have just begun research on these topics. The book is written by active researchers in the field of colloids and interfacial chemistry, based on the practical experience of the authors. In each chapter, the key points of measurement, how to analyze data correctly, points to be careful about, and merits of a particular method are concisely explained from the point of view of the readers. Not only in industries such as cosmetics and pharmaceuticals but also in academic studies of nanotechnology, correct understanding of colloid and interface phenomena is vital because the properties of these items, however small, are affected by the nature of interfaces. This book will be particularly useful for researchers who are not yet fully confident of the measurement techniques that are clearly explained here. .